Pure Sociology: Subjectivity at Risk? - James J. Chriss (Academicus International Scientific Journal)

(untitled)
Sociology began as a scientific discipline in large part by defining itself by what it was NOT, namely, psychology. This means that within sociology there has always been an uncertainty over whether subjective phenomena, including selves, identities, emotions, consciousness, feelings, or experience, are topics worthy of scientific analysis and observation within the discipline. Some argue that psychology is vital to doing sociology (as an accepted or foundational “first principle”), while others reject it because it falls outside the scope of sociological concerns. In this paper I analyze antisubjectivism in sociology in the form of Donald Black’s “pure sociology,” as well as the antihumanist network theory of Stephan Fuchs. I conclude by suggesting that if sociologists are serious about achieving their long sought after but elusive “science of society,” then the sort of antisubjectivism, antihumanism, and antiessentialism being propounded by Black, Fuchs, and others should receive serious consideration in current and future sociological work.